A new delay parameter dependent on variable analysis periods at signalized intersections. Part 1: Model development - Akgüngör, Ali P. (Transport, 2008)
Delay is an important factor in the optimization of traffic signals and the determination of the level of service of a signalized intersection. This paper proposes a methodology and a new formulation to identify the delay parameter in signalized intersection delay models. In this study, the delay parameter is modeled as a function of analysis period instead of a fixed value used by the existing delay models. Therefore, the proposed delay model including new delay parameter can produce more reasonable delay estimations at signalized intersections for variable time periods. A comparative study of the proposed time‐dependent model against the existing four different models was performed to present the improvements in this model. First published online: 27 Oct 2010